The effect of smoking on COVID-19 infection: a systematic review and meta-analysis of meta-analyses studies - Massoud Sokouti; Babak Sokouti; Mohsen Sokouti (Discover Applied Sciences)
Abstract Background In two recent years, many more meta-analysis studies have been published on the effect of mortality and severity of smoking on COVID-19 infection. This study aimed to meta-analyze the available meta-analyses data investigating the influence of tobacco on COVID-19 infection severity and mortality. Methods We searched three databases (PubMed, Google Scholar, and Scopus) to find meta-analysis studies that examined the efficacy of smoking on COVID-19 infection. In this meta-analysis, we merged the findings of each meta-analysis based on the odds ratio of mortality and severity. A subgroup meta-analysis comparing continents was also carried out to uncover publication bias. Results Six meta-analyses met for eligibility. A random effect meta-analysis of the severity and mortality of COVID-19 showed: (OR = 1.579, P < 0.001, and OR = 1.452. P = 0.001), which showed smoking increased the severity and mortality of COVID-19 infection. This article combined all the results of previous meta-analyses and showed the effect of these two risk factors of tobacco on COVID-19 disease. Subgroup analyses between continents were also performed. Using the trim-and-fill approach, researchers can use a basic funnel plot to determine publication bias. We also performed the subgroup analysis to detect heterogeneity among continents. We think there is sufficient data to make the effectiveness of the overall meta-analysis results. Conclusions Smoking was shown to harm the severity and mortality of COVID-19 infections, according to this meta-analysis.